2013
DOI: 10.1002/jbm.b.32918
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel active release coating to prevent biofilm implant‐related infections

Abstract: Biofilm implant-related infections cost the US healthcare system billions of dollars each year. For several decades, device coatings have been developed that actively release antimicrobial compounds in an attempt to prevent these infections from developing. To date, few coatings have been put into clinical use. These have shown limited to no efficacy in clinical trials. Recent data have shown the in vitro and in vivo efficacy of a novel active release coating that may address the limitations of coatings that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Additionally, this low-molecular-mass compound has potent activity against bacterial biofilms (32,33). Some previous studies undertook evaluations of CSA-13 activity using in vitro systems and different experimental settings dedicated to evaluation of activity against resistant strains (31,34), in different body fluids (32), in the presence of different polyelectrolytes (35,36), or using drug release systems and antimicrobial coating (32,37,38). However, only a few studies have evaluated the activity of CSA-13 in cell cultures or animal models (13,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this low-molecular-mass compound has potent activity against bacterial biofilms (32,33). Some previous studies undertook evaluations of CSA-13 activity using in vitro systems and different experimental settings dedicated to evaluation of activity against resistant strains (31,34), in different body fluids (32), in the presence of different polyelectrolytes (35,36), or using drug release systems and antimicrobial coating (32,37,38). However, only a few studies have evaluated the activity of CSA-13 in cell cultures or animal models (13,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Williams et al [99] characterized physical and chemical properties of a coating containing CSA-13 as a novel active release agent in a medical grade polymer coating on fracture fixation plates. Studies of polymerization of the silicone coating demonstrated that incorporation of CSA-13 (18% w/w) did not impact the physical properties of the coating.…”
Section: Medical Device Coatings Containing Cerageninsmentioning
confidence: 99%
“…Recently, antimicrobial nanoparticles were synthesised using ceragenins and they were introduced as multifunctional theranostics [33]. Different applications of ceragenins include contact lenses, hydrogels with an antibacterial innate immune function [34], polymeric coating applied to implanted devices to prevent perioperative device-related infections [35], thermally, chemically, and physically stable medical grade polydimethylsiloxane (PDMS) material to prevent biofilm formation [36], silicon [37], and gene delivery systems [38] (Figure 2). Similarly to cathelicidin-related antimicrobial peptides [15], ceragenins that mimic the hydrophobic and cationic morphology of cathelicidin have antiproliferative effects on the colon cancer-derived cell line HCT116.…”
Section: Cerageninsmentioning
confidence: 99%